2013
DOI: 10.1021/am401434y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Interface Morphologies of Silicon Films on Arbitrary Substrates: Application in Solar Cells

Abstract: A three-dimensional model that predicts the interface morphologies of silicon thin-film solar cells prepared on randomly textured substrates was developed and compared to experimental data. The surface morphologies of silicon solar cells were calculated by using atomic force microscope scans of the textured substrates and the film thickness as input data. Calculated surface morphologies of silicon solar cells are in good agreement with experimentally measured morphologies. A detailed description of the solar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 36 publications
(102 reference statements)
1
31
0
Order By: Relevance
“…Because of the low absorption coefficient of amorphous silicon for longer wavelength (k = 700 nm), light needs to finish numerous path in the solar cell. The approaching light achieves the back contact of the sunbased cell, where it gets reflected and completed different paths inside the solar cell (Dewan et al 2012;Jovanov et al 2013c;Tamang et al 2016b). From Fig.…”
Section: Solar Cell With Pyramid Texture Substratementioning
confidence: 99%
“…Because of the low absorption coefficient of amorphous silicon for longer wavelength (k = 700 nm), light needs to finish numerous path in the solar cell. The approaching light achieves the back contact of the sunbased cell, where it gets reflected and completed different paths inside the solar cell (Dewan et al 2012;Jovanov et al 2013c;Tamang et al 2016b). From Fig.…”
Section: Solar Cell With Pyramid Texture Substratementioning
confidence: 99%
“…For the multiscale textured substrates, the glass substrate is modeled by hexagonally arranged concave craters. The surface morphology of FTCO layer is determined by the surface coverage algorithm [25,26] because the growth of the ZnO:B film deposited by LPCVD process takes place in the direction of local surface normal [27]. The resulting microtextures of the FTCO layer have diameters of almost 3 mm and height of 1.2 mm.…”
Section: Realistic Interface Morphologies Of Nanoscale and Multiscalementioning
confidence: 99%
“…In recent years, the formation of silicon thin film solar cells on nanoscale textured substrates has been studied. Different models have been proposed to describe the film growth and interface morphologies of silicon thin films deposited on textured substrates [11,15,16,25,26,28,29]. Most of the studies have shown that amorphous silicon grows (almost entirely) in the direction of a local surface normal.…”
Section: Realistic Interface Morphologies Of Nanoscale and Multiscalementioning
confidence: 99%
See 1 more Smart Citation
“…The model was recently enhanced by directional growth factors for simulating columnar µc-Si growth while neglecting so-called nanofeatures (cf. [7]). The distinction between columnar growth and nanofeatures is important, as the columnar film growth is directional and in principle covered by existing models, while nanofeatures arise in a less predictable fashion.…”
Section: Introductionmentioning
confidence: 99%